Word Usage of ‘Ксива’ and ‘Малява’ in Russian Criminal Discourse - Zubkov, Eugene (Respectus Philologicus, 2013)
This paper analyzes the dynamics of usage of the lexical units ксива and малява (types of slip) in Russian criminal discourse. We are led to believe that, despite the large variety in understanding of the term “discourse,” it can be defined as a sphere of human linguosemiotic experience which is determined by the pragmatics of activity carried out within it, the socio-psychological features of the participants of interactions, the specifics of time and space, and topics according to the methodology proposed by O. Leszczak. Nowadays, a growing interest in criminal discourse has been observed and implies “complex research on the discourse about crime, which enables better understanding of its participants, their criminal positions and functions, the problematics and issues for discussions about crime, along with its influence on modern criminology and crime prevention” (Жалинский 2009). All these factors should be taken into account, making the researcher verify the sources of language material in order to avoid distorting meanings in the word usage under study. This is caused by the notional sphere itself, which, in certain types of discourse, can be verbalized by the word group, which may be represented by a word expression, phrase, speech segment, etc. Words and word expressions considered as phraseological units of criminal discourse were analyzed in this paper.
Keywords: Word Usage; Sense; Discourse; ксива; малява